Consumption of barley flour increases gut fermentation and improves glucose intolerance via the short-chain fatty acid receptor GPR43 in obese male mice. Issue 21 (18th October 2022) - Mio, Kento; Iida-Tanaka, Naoko; Yamanaka, Chiemi; Kimura, Ikuo; Aoe, Seiichiro
Abstract : The ameliorative effect of barley intake on glucose intolerance is attenuated when Gpr43 is deficient. Abstract : Barley consumption is expected to increase insulin sensitivity by increasing the level of short-chain fatty acids (SCFAs) and promoting the secretion of GLP-1. However, the involvement of GPR43, a receptor for SCFAs, has not been investigated. Therefore, we evaluated whether the inhibitory effect of β-glucan-rich barley intake on blood glucose rise is mediated by GPR43 signalling via an increase of SCFAs. C57BL/6J mice and GPR43-knockout mice were fed high-fat diets with either cellulose (HC) or β-glucan-rich barley flour (HB) for 12 weeks. The level of SCFAs in cecum contents was measured and the concentration of GLP-1 in the portal vein was determined. The supernatant of the cecum contents of C57BL/6J mice was added to GLUTag cells, and then the changes to GLP-1 and intracellular Ca 2+ concentrations determined. The same parameters were measured using cells in which GPR43 was knocked down by siRNA. C57BL/6J mice fed HB diets showed a suppressed glucose rise compared to those on the HC diet. Cecum SCFAs and GLP-1 concentration in the portal vein were also increased by the HB diet. When an aqueous solution from the cecum content of mice fed a HB diet was added to GLUTag cells, GLP-1 secretion and intracellular Ca 2+ concentration were increased. These phenomena were not observed in cells with knockdown of GPR43. In GPR43 knockout mice an increase of GLP-1 in the portal vein and suppression of blood glucose elevation was attenuated, despite increased SCFAs brought on by the HB diet. In conclusion, GPR43 activation in the intestinal tract via increased SCFAs is required for the glucose intolerance-improving effect of barley consumption.